ANALISIS IMPLEMENTASI KEBIJAKAN KONSERVASI PENYU (Studi Di Desa Emang Lestari Kecamatan Lunyuk Kabupaten Sumbawa) (Indonesian Journal of Social Sciences and Humanities, 2020)
The aims of this study were: to described the implementation of the turtle conservation policy in Emang Lestari Village, Lunyuk District, Sumbawa Regency, describing  the factors that influences the implementation of the turtle conservation policy in Emang Lestari Village, Lunyuk District, Sumbawa Regensy, and describing the strategies used to minimize the hunting both of turtle eggs and meat in Emang Lestari Village, Lunyuk District, Sumbawa Regency. The technique of collecting data were observation, interview and documentation. The results of the study were: (1) regulations relate to  policy of turtle conservation area in Emang Lestari Village, starting frm the law auntil the circular latter has been made, However, the implementation of a polcy that made has not gone well; (2) there were 2 factors that influence the implementation of turtle conservation policy, namely internal factors (resources, communication, bureaucracy and position) and exernal factors (community  culture and economy); and (3) the strategies implemented to minimize hunting of turtle eggs and meat were by empowerment of Communities around the Turtle Conservation Area, Supervision Strengthening through Local Government policies, Making Research, Reviews for Conservation Area and Strengthening  Law Enforcement.